2012
DOI: 10.1113/jphysiol.2012.238444
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic control of AMPA receptor responsiveness in mouse spinal cord motoneurons

Abstract: Key points• The muscarinic receptors increase the excitability in spinal cord motoneurons.• In the present study, I report the muscarinic modulation of postsynaptic AMPA receptors at glutamatergic synapses on spinal cord motoneurons.• The muscarinic modulation acts specifically on synapses originated at the dorsolateral funiculus, which contains supraspinal and spinal intersegmental influences.• The present results suggest that the modulatory actions of muscarinic receptors reduce the synaptic weight of excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The first showed that the activation of projections from cholinergic neurons located near the central canal potentiates commissural glutamatergic inputs to motor neurons via muscarinic receptor‐dependent mechanisms (Bertrand & Cazalets, ). Conversely, the second study showed that muscarinic receptor activation can inhibit synaptic currents mediated by postsynaptic AMPA receptors on motor neurons (Mejia‐Gervacio, ). Further work will be required to determine whether either of these cholinergic modulatory effects on synaptic transmission involves the C bouton system.…”
Section: Bouton Functionmentioning
confidence: 99%
“…The first showed that the activation of projections from cholinergic neurons located near the central canal potentiates commissural glutamatergic inputs to motor neurons via muscarinic receptor‐dependent mechanisms (Bertrand & Cazalets, ). Conversely, the second study showed that muscarinic receptor activation can inhibit synaptic currents mediated by postsynaptic AMPA receptors on motor neurons (Mejia‐Gervacio, ). Further work will be required to determine whether either of these cholinergic modulatory effects on synaptic transmission involves the C bouton system.…”
Section: Bouton Functionmentioning
confidence: 99%
“…We found that M2 receptor activation decreased, while M3 receptor activation increased, the frequency of PSCs to motoneurons. This could reflect direct modulation of synaptic transmission, given that M2 receptor activation decreases glutamatergic transmission from primary sensory afferents to dorsal neurons 66 and decreases evoked AMPA-mediated synaptic currents recorded from mouse motoneurons after stimulation of the spinal cord dorsolateral funiculus 67 , while blockade of M3 receptors was shown to affect motoneuron potentials in response to stimulation of spinal commissural interneurons 13 . However, given significant expression of M2 receptors in the mid-lumbar spinal cord of rats 68 , and the demonstration that M3 receptors excite lumbar motor networks resulting in the generation of bursts of ventral root activity in the rat 26 , activation of M2 and M3 receptors could also differentially alter the activity of interneurons resulting in indirect changes in synaptic drive to motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic receptor binding properties are also decreased in the L5–6 segments, where ankle extensor MNs are predominantly located; since these decreases were accompanied by M2 receptor protein redistribution between synaptic and extrasynaptic areas on MNs surface, the possibility remains that this type of compensatory responses develop also after stimulation and may influence MN excitability [36]. Moreover, because muscarinic M2 receptors are localized not only at the cholinergic but also at the glutamatergic (Glu) synapses [37], and control AMPA receptor responsiveness [38], their changed expression may contribute to altered glutamatergic signaling and excitatory properties of MNs. An individual analysis of the amplitude of complex responses gave us an indication of increased excitability of the H-reflex loop.…”
Section: Discussionmentioning
confidence: 99%